Factors affecting the implementation of the National Tuberculosis Control Programme by professional nurses - Sekotlong, Raesetja Jacobeth (My University, 2014)
The present study presents data about the factors that are affecting the implementation of the National Tuberculosis Control Programme by the professional nurses in the Mogalakwena Municipality of the Waterberg District in the Limpopo Province. Despite the intervention by the then Waterberg District Department of Health and Social Development through continual training and workshops of professional nurses in respect of the NTCP, there are still more challenges observed in terms of TB management. Aim of the study The aim of the study was to identify and describe the factors that are affecting the implementation of the NTCP and the findings may be utilised to describe the strategies to increase TB cure rate in the Mogalakwena Municipality of the Waterberg District. Research Methodology A quantitative research approach was used to conduct this study. One hundred and thirty one professional nurses employed at 28 clinics of the Mogalakwena Municipality were selected to participate in the study. The researcher distributed the questionnaires at the clinics. A structured questionnaire with both open and closed-ended questions was administered. The questionnaire was pretested in the Mahwelereng Local Area which did not form part of the main study. Results Of the 131 respondents, 33.6% were the largest age group of between 40 – 50 years followed by 24.4% who were older than 50 years in contrast with the smallest age group of 18 – 28 years that comprised 18.3% of the population. Sixteen per cent of the respondents were male while 84.0% were female. The findings show that 83.2% of respondents held a diploma in nursing while 16.8% had a degree in nursing. The findings indicate that 98.4% of the respondents were reported to be having knowledge about TB while 1.6% reported not having knowledge. The findings v indicate that 98.4% of the respondents had knowledge about TB suspect screening according to the NTCP in contrast with 1.6% of the participants who did not have knowledge about TB screening. About 95.4% of the respondents reported tracing of TB defaulters while 4.6% of the respondents reported that TB defaulters were not traced. Sixty point three per cent 63.3% of the respondents thought that a negative attitude of professional nurses was the main cause of poor implementation of the NTCP while 30.5% of them disagreed with the statement. Conclusion Respondents demonstrated non-compliance to the implementation of the NTCP, ignorance to acquire skills and negative attitude towards the programme that was consistently significant with other similar studies. The study recommends an updated training programme of all TB trained nurses, as well as values clarification about the importance of the implementation of the NTCP in the management of the TB disease.
Thesis (M. Cur.) -- University of Limpopo, 2014
Keywords: Tuberculosis control programme; Tuberculosis -- Prevention.; Primary health care.; Tuberculosis patients.